An Unusual Cause of Headache: Ruptured Intracranial Teratoma: A Case Report (Bangladesh Journal of Radiology and Imaging, 2026)
Intracranial teratoma are uncommon intracranial neoplasms usually present in childhood or early adulthood and typically smaller. MRI and MRV of Brain of an 18-year-old male to evaluate chronic intermittent headache for 4 years founds rupture intracranial teratoma.